2018
DOI: 10.1055/s-0038-1660809
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Transthoracic Device Closure and Surgical Repair with Right Submammary or Right Infra-axillary Thoracotomy for Perimembranous VSD

Abstract: TTDC, SRRIAT, and SRSMT all showed excellent outcomes and cosmetic appearances for selected VSD patients. TTDC had advantages over SRRIAT and SRSMT in terms of short operation duration and smaller incision size and shorter durations of intensive care and hospital stays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…All the procedure were successful with little complications. The success rate of TTCVSD with lower sternal incision was the same even compared with surgical repair with right infra-axillary thoracotomy or with right submammary thoracotomy [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the procedure were successful with little complications. The success rate of TTCVSD with lower sternal incision was the same even compared with surgical repair with right infra-axillary thoracotomy or with right submammary thoracotomy [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The transcatheter closure of VSD has had an increasing popularity recently due to the advancement of transcatheter techniques, but especially patients with low body weight and VSD near the aortic valves are usually not suitable for this method (8). Chen et al ( 9) compared percutaneous device occlusion with minimally invasive techniques for VSD closure and reported that the minimally invasive technique was more cost-effective than device occlusion but with similar complication rates.…”
Section: Commentmentioning
confidence: 99%
“… 4) Increasing procedural success using these devices have encouraged cardiac surgeons to employ these devices through minimally invasive incisions without resorting to extracorporeal circulation. 5) Such perventricular device closures show similar procedural outcomes compared to conventional surgery. 6) …”
Section: Introductionmentioning
confidence: 96%